Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Effect of acipimox on skeletal muscle biochemistry, structure and function in older people with probable sarcopenia: an experimental medicine study - Claire McDonald; Craig Alderson; Matthew G. Birkbeck; Silvia Del Din; Gráinne S. Gorman; Kieren G. Hollingsworth; Cameron Kirk; Clare Massarella; Lynn Rochester; Helen A. L. Tuppen; Charlotte Warren; Avan A. Sayer; et al. (GeroScience, 2025)
Background Skeletal muscle nicotinamide adenine dinucleotide (NAD) concentrations are low in people with sarcopenia. Increasing NAD concentrations may offer a novel therapy. This study tested if acipimox (a NAD precursor) improves skeletal muscle NAD concentration and function in people with probable sarcopenia. Participants aged 65 and over with low walk speed (< 0.8 m/s) and low muscle strength (by 2019 European Working Group criteria) were recruited to this before and after, proof-of-concept study. Participants received acipimox 250 mg orally (twice or thrice daily according to creatinine clearance) + aspirin 75 mg daily (to prevent facial flushing) for 4 weeks. Muscle biopsy of the vastus lateralis, 31 P magnetic resonance spectroscopy and a 7-digital mobility assessment were performed before starting acipimox and after 3 weeks of treatment. The primary outcome was change in skeletal muscle NAD concentration. Secondary outcomes included change in phosphocreatine recovery rate and measures of physical performance. Eleven participants (8 women), mean age 78.9 years (SD 4.3), were recruited. Mean walk speed at baseline was 0.69 m/s (SD 0.07). All completed baseline and follow-up visits. Median medication adherence was 95% (range 91–104%). There was no statistically significant difference in the primary outcome of change in NAD concentrations in skeletal muscle between baseline and follow-up [median difference: − 0.003 umol/g (IQR − 0.058 to 0.210); P = 0.26] or secondary outcomes. Nineteen none-serious adverse events were reported. Although the study protocol was feasible and well tolerated, acipimox did not improve skeletal muscle NAD concentration, biochemical markers or physical function in people with probable sarcopenia. ClinicalTrials.gov Identifier: ISRCTN (ISRCTN87404878).

Microplastic biomonitoring studies in aquatic species: A review & quality assessment framework - Benjamin de Jourdan; Danielle Philibert; Davide Asnicar; Craig Warren Davis (Science of The Total Environment, 2024)

Automatic segmentation of radar data from the Chang’E-4 mission using unsupervised machine learning: A data-driven interpretation approach - Iraklis Giannakis; Ciaran McDonald; Jianqing Feng; Feng Zhou; Yan Su; Javier Martin-Torres; Maria-Paz Zorzano; Craig Warren; Antonios Giannopoulos; Georgios Leontidis (Icarus, 2024)

Surface-layer turbulence associated with a fast spreading grass fire - Shiyuan Zhong; Melissa Gonzalez-Fuentes; Craig B. Clements; Xindi Bian; Warren E. Heilman; Joseph J. Charney; Mario M. Valero; Adam K. Kochanski; Michael T. Kiefer (Agricultural and Forest Meteorology, 2024)

Evidence of shallow basaltic lava layers in Von Kármán crater from Yutu-2 Lunar Penetrating Radar - Iraklis Giannakis; Javier Martin-Torres; Yan Su; Jianqing Feng; Feng Zhou; Maria-Paz Zorzano; Craig Warren; Antonios Giannopoulos (Icarus, 2024)

Stochastic hyperbola fitting, probabilistic inversion, reverse-time migration and clustering: A novel interpretation toolbox for in-situ planetary radar - Iraklis Giannakis; Javier Martin-Torres; Maria-Paz Zorzano; Yan Su; Craig Warren; Antonios Giannopoulos (Icarus, 2023)

Features of turbulence during wildland fires in forested and grassland environments - Ajinkya Desai; Warren E. Heilman; Nicholas S. Skowronski; Kenneth L. Clark; Michael R. Gallagher; Craig B. Clements; Tirtha Banerjee (Agricultural and Forest Meteorology, 2023)

Contribution of soil bacteria to the atmosphere across biomes - Stephen D.J. Archer; Kevin C. Lee; Tancredi Caruso; Antonio Alcami; Jonathan G. Araya; S. Craig Cary; Don A. Cowan; Claudia Etchebehere; Batdelger Gantsetseg; Benito Gomez-Silva; Sean Hartery; Ian D. Hogg; et al. (Science of The Total Environment, 2023)

Quantification of meteorological drought risks between 1.5 °C and 4 °C of global warming in six countries - Jeff Price; Rachel Warren; Nicole Forstenhäusler; Craig Wallace; Rhosanna Jenkins; Timothy J. Osborn; D. P. Van Vuuren (Climatic Change, 2022)
We quantify the projected impacts of alternative levels of global warming upon the probability and length of severe drought in six countries (China, Brazil, Egypt, Ethiopia, Ghana and India). This includes an examination of different land cover classes, and a calculation of the proportion of population in 2100 (SSP2) at exposed to severe drought lasting longer than one year. Current pledges for climate change mitigation, which are projected to still result in global warming levels of 3 °C or more, would impact all of the countries in this study. For example, with 3 °C warming, more than 50% of the agricultural area in each country is projected to be exposed to severe droughts of longer than one year in a 30-year period. Using standard population projections, it is estimated that 80%-100% of the population in Brazil, China, Egypt, Ethiopia and Ghana (and nearly 50% of the population of India) are projected to be exposed to a severe drought lasting one year or longer in a 30-year period. In contrast, we find that meeting the long-term temperature goal of the Paris Agreement, that is limiting warming to 1.5 °C above pre-industrial levels, is projected to greatly benefit all of the countries in this study, greatly reducing exposure to severe drought for large percentages of the population and in all major land cover classes, with Egypt potentially benefiting the most.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Quantification of impacts between 1.5 and 4 °C of global warming on flooding risks in six countries - Yi He; Desmond Manful; Rachel Warren; Nicole Forstenhäusler; Timothy J. Osborn; Jeff Price; Rhosanna Jenkins; Craig Wallace; Dai Yamazaki (Climatic Change, 2022)
We project climate change induced changes in fluvial flood risks for six global warming levels between 1.5 and 4 °C by 2100, focusing on the major river basins of six countries. Daily time series of precipitation, temperature and monthly potential evapotranspiration were generated by combining monthly observations, daily reanalysis data and projected changes in the five CMIP5 GCMs also selected in the ISI-MIP fast track project. These series were then used to drive the HBV hydrological model and the CaMa-Flood hydrodynamic model to simulate river discharge and flood inundation. Our results indicate that return periods of 1 in 100-year floods in the late twentieth century (Q100-20C) are likely to decrease with warming. At 1.5 °C warming, 47%, 66%, 27%, 65%, 62% and 92% of the major basin areas in Brazil, China, Egypt, Ethiopia, Ghana and India respectively experience a decrease in the return period of Q100-20C, increasing to 54%, 81%, 28%, 82%, 86% and 96% with 4 °C warming. The decrease in return periods leads to increased number of people exposed to flood risks, particularly with 4 °C warming, where exposure in the major river basin areas in the six countries increases significantly, ranging from a doubling (China) to more than 50-fold (Egypt). Limiting warming to 1.5 °C would avoid much of these increased risks, resulting in increases ranging from 12 to 1266% for the 6 countries.

Cerebellar Contributions to Motor Impairments in People with Multiple Sclerosis - Alexandra C. Fietsam; Warren G. Darling; Jacob J. Sosnoff; Craig D. Workman; John Kamholz; Thorsten Rudroff (The Cerebellum, 2021)

Correction to: Modification of the third phase in the framework for vertebrate species persistence in urban mosaic environments - Colleen T. Downs; Jarryd Alexander; Mark Brown; Moses Chibesa; Yvette C. Ehlers Smith; S. Thobeka Gumede; Lorinda Hart; Kyrone K. Josiah; Riddhika Kalle; Machawe Maphalala; Mfundo Maseko; Shane McPherson; et al. (Ambio, 2021)

Modification of the third phase in the framework for vertebrate species persistence in urban mosaic environments - Colleen T. Downs; Jarryd Alexander; Mark Brown; Moses Chibesa; Yvette C. Ehlers Smith; S. Thobeka Gumede; Lorinda Hart; Kyrone K. Josiah; Riddhika Kalle; Machawe Maphalala; Mfundo Maseko; Shane McPherson; et al. (Ambio, 2021)

Passive Acoustic Monitoring Reveals Spatio-Temporal Distributions of Antarctic and Pygmy Blue Whales Around Central New Zealand - Victoria E. Warren; Ana Širović; Craig McPherson; Kimberly T. Goetz; Craig A. Radford; Rochelle Constantine (Frontiers in Marine Science, 2021)
Effective management of wild animal populations relies on an understanding of their spatio-temporal distributions. Passive acoustic monitoring (PAM) is a non-invasive method to investigate the distribution of free-ranging species that reliably produce sound. Critically endangered Antarctic blue whales ( Balaenoptera musculus intermedia ) (ABWs) co-occur with pygmy blue whales ( B. m. brevicauda ) (PBWs) around New Zealand. Nationally, both are listed as “data deficient” due to difficulties in access and visual sub-species identification. PAM was used to investigate the distributions of blue whales via sub-species specific song detections in central New Zealand. Propagation models, incorporating ambient noise data, enabled the comparison of detections among recording locations in different marine environments. ABW detections peaked during austral winter and spring, indicating that New Zealand, and the South Taranaki Bight (STB) in particular, is a migratory corridor for ABWs. Some ABW calls were also detected during the breeding season (September and October). PBW calls were highly concentrated in the STB, particularly between March and May, suggesting that an aggregation of PBWs may occur here. Therefore, the STB is of great importance for both sub-species of blue whale. PBW detections were absent from the STB during parts of austral spring, but PBWs were detected at east coast locations during this time. Detection area models were valuable when interpreting and comparing detections among recording locations. The results provide sub-species specific information required for management of critically endangered ABWs and highlight the relative importance of central New Zealand for both sub-species of blue whale.

The mechanism of seed coat‐imposed dormancy revealed by oxygen uptake in Chatham Island forget‐me‐not Myosotidium hortensia (Decne.) Baill. - Craig R. McGill; Myoung J. Park; Warren M. Williams; Heather A. Outred; Jayanthi Nadarajan (New Zealand Journal of Botany, 2018)
Chatham Island forget‐me‐not Myosotidium hortensia (Boraginaceae) is a monotypic genus endemic to the Chatham Islands of New Zealand. Myosotidium hortensia is threatened in its natural environment by introduced grazing animals and weeds. Further to this, the conservation and reintroduction efforts of M. hortensia are hindered by their dormant seeds. The dormancy is imposed by the seed coat but the underlying dormancy mechanisms are not well understood. Understanding the dormancy mechanisms in this species will help in revegetation efforts. This work aims to elucidate mechanisms by which the seed coat imposes dormancy in M . hortensia by determining the germination after manipulation of the seed coat and measuring changes in oxygen uptake in response to this manipulation. The structure of the seed coat was assessed using scanning electron microscopy and the presence or absence of lignin in the seed coat determined. As with other Boraginaceae, the seed coat of M . hortensia does not restrict water penetration into the seed. Oxygen uptake was 4.5 fold higher in decoated than in intact seed. There was no significant increase in oxygen uptake for the seeds when their seed coat had been pierced or pierced and resealed with vaseline. However, the germination rate, as measured by radicle emergence, was faster in these seeds. These findings, in addition to the structural analysis of the seed coat which revealed that the seeds have secondary thickening but no lignin, confirmed that mechanical constraint of embryo growth was preventing germination.

Basolateral amygdala volume and cell numbers in major depressive disorder: a postmortem stereological study - Marisa J. Rubinow; Gouri Mahajan; Warren May; James C. Overholser; George J. Jurjus; Lesa Dieter; Nicole Herbst; David C. Steffens; Jose J. Miguel-Hidalgo; Grazyna Rajkowska; Craig A. Stockmeier (Brain Structure and Function, 2016)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Simulations of minerals using density-functional theory based on atomic orbitals for linear scaling - M. S. Craig; M. C. Warren; M. T. Dove; J. D. Gale; D. Sanchez-Portal; P. Ordejon; J. M. Soler; E. Artacho (Physics and Chemistry of Minerals, 2004)